Awareness and screening behaviors of breast cancer among urban women in Mysuru, India- need for breast health education program - B., Madhu; Shankar, Puja (International Journal Of Community Medicine And Public Health, 2017)
Background:Breast cancer is the second most common cancer among Indian women. By recommending them to participate in screening programs, early detection can be possible. The objectives of the study were to determine awareness of ‘breast cancer and breast cancer-screening procedures’ among urban women of Mysore; to determine the extent to which ‘breast cancer screening procedures’ are practiced; to determine the factors associated with better screening practices. Methods:Cross sectional study was conducted (August 15th-September 15th, 2011) in Mysore. Study group comprised of 100 professional women, without history of breast cancer. Results:Ninety nine percent of women were aware of breast cancer. Sixty three percent of women were aware of breast self-examination. Sixty six percent had practiced BSE once; only 18 percent of them were aware of ideal positions. Conclusions:It was found that low levels of practice directly associated with the lack of knowledge regarding breast cancer and thus emphasizing the need for a community based breast health education (BHE) program for women.